Understanding Canadian Surrogacy Consultants' Perspectives on Their Role and the Law - Czarnowski, Alicia Jennifer (Université d'Ottawa / University of Ottawa, 2026)
This dissertation analyses the empirical data arising out of eight semi-structured interviews with Canadian surrogacy consultants. It provides insight into surrogacy consultants' perspectives and practices, and explores how consultants' first-hand accounts align with the existing narratives about surrogacy consultancies. Ultimately, my participants' voices provide nuance to ongoing debates and discussions. Many first-hand accounts challenge some prevalent criticisms, revealing a strong desire to help surrogates, in particular, as well as practices that can provide valuable support. However, other accounts indicate practices and that may be harmful for surrogates and intended parents, suggesting a need for increased oversight. In addition, this dissertation highlights how consultants understand and implement the law. Participants shared multiple justifications for their businesses' legality, based on their understandings of the law. Their discussions suggest that Canada's prohibition of paid surrogacy intermediaries is generally ineffective, in that the current legal regime fails to deter undesirable activities while simultaneously limiting access to potentially beneficial services. These findings cumulatively support calls for the regulation of surrogacy consultancies.
Keywords: surrogacy; surrogacy consultants; assisted human reproduction; Assisted Human Reproduction Act